Formação continuada de professores da educação infantil: um estudo de caso sobre o projeto especial de ação do município de São Paulo - Alves, Claudia Oliveira Fernandes (Universidade Federal de São Carlos, 2024)
This study focuses on the Projeto de Ação Especial/PEA (Special Action Project) and aims to investigate its contribution to the continuing in-service training of kindergarten teachers in the city of São Paulo. The main objective of this investigation is to understand how the training actions developed by the PEA are carried out in the continuing in-service training at the Centro de Educação Infantil/CEI Girassol (Girassol Early Childhood Education Center). The choice and delimitation of the theme is based on the researcher’s experiences in teaching in Early Childhood Education at different moments in her teaching career, and which permeates the construction of her own conception of what it means to be a teacher, especially from her work in the Municipal Education Network of São Paulo as a teacher and pedagogical coordinator. This work methodology guiding is based on a qualitative approach, using the case study method (YIN). In order to collect the data, we used instruments such as a field diary, official documents from São Paulo Rede Municipal de Educação/RME (Municipal Education Network), CEI Girassol Pedagogical Political Project, documents and records that organize the educational unit’s continuing in-service training, as well as semi-structured interviews with five teachers and the pedagogical coordinator, participating at the PEA training. The main contributions to the theoretical framework that underpins this research include authors such as Nóvoa (1995, 2002, 2009, 2014, 2019), Tardif (2014), Zeichner (2008) Gatti (2011), Placco (2010) and others. The choice of these authors is based on their contributions that help to broaden the understanding of the conceptions that underpin the debate on continuing teacher training, especially those that shed light on the discussions about continuing in-service training in early childhood education. This study is expected to contribute to the construction of a new approach to the continuing education of kindergarten teachers in the city of São Paulo, based on official regulations, such as the Portaria nº 901, from January 24th, 2014, and the Instrução Normativa nº 14, from March 4th, 2022, which have established the Projeto de Ação Especial/PEA (Special Action Project) as an instrument for continuing in-service training. The results and discussions, based on the guiding question, point to reflections on the Projeto de Ação Especial/PEA (Special Action Project) as an important instrument that contributes to the continuing in-service training of kindergarten teachers in the city of São Paulo. Therefore, there is an understanding that the dimension of the work of continuing education and in-service training based on the PEA revealed itself as the expression of the priorities outlined by the guidelines established by Portaria nº 901, in alignment with the Political-Pedagogical Project of the Educational Unit and the curricular guidelines for Early Childhood Education, without, however, forgetting the increase in the levels of quality of care for children aged zero to three at CEI Girassol.
Continuing teacher education in early childhood education: a case study of the special action project in São Paulo municipality
Keywords: Educação infantil; Formação continuada de professores; Formação em serviço; Projeto Especial de Ação; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade